Behavioral orientations and peer-contact patterns of relationally aggressive girls - Isobe, Miyoshi (Animo Repository, 2004)
The present study was designed to assess the behavioral orientations and peer-contact patterns of relationally aggressive girls. Based on teachers' assessments of relational aggression, 16 preschool girls were assigned to either a relationally aggressive group or a nonaggressive group and then observed in a free play setting. Several aspects of their interactive behaviors, e.g., cooperative play and social conversation, and noninteractive behaviors, e.g., solitary play and transition, were observed. Analysis indicated the relationally aggressive group spent more time engaged in social conversation and transition and less time in cooperative play than did the nonaggressive group. Further, findings indicated that the relationally aggressive group spent more time with one particular peer than did the nonaggressive group.